Exploring the Satisfaction and Dissatisfaction Factors Derived from Food and Beverage Services of Thermal Hotels - Ozan Kaya (DETUROPE)
The increase in supply and demand in thermal tourism has led to the intensification of competition. This situation causes the thermal hotels to spend more effort on issues such as understanding customer expectations and providing customer satisfaction. Food and beverage services have great importance in all areas of tourism as well as in thermal hotels. Thus, the main purpose of the study is to reveal the factors affecting the tourists’ satisfaction or dissatisfaction in food and beverage services in thermal hotels. The research was conducted in thermal hotels in Denizli, Turkey. Tourists’ online reviews on TripAdvisor were analysed by content analysis. The findings clearly show the main areas of satisfaction of the food and beverage services in the thermal hotels as taste of food, employees, quality of food and activities in the restaurants. However, the main areas where the online reviewers are dissatisfied are high price, variety of food, capacity for restaurants and freshness of food. Then, one-way ANOVA was performed to determine whether satisfaction levels of food and beverage service has an affect on overall hotel performance in the different categories of review. Results show the strong relationship between customers’ satisfaction on food and beverage services and overall thermal hotel satisfaction. The abstract of this study was presented in Cultural Management and Governance for European Thermal Tourism: Creativity and Innovation for cultural and tourism management in European Thermal Routes and Sites Conference, Cori, Italy, 6 November 2017.